1998
DOI: 10.1006/viro.1997.8997
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar Localization of Mouse Mammary Tumor Virus Proteins in T-Cell Lymphomas

Abstract: To characterize novel proteins expressed in lymphoma cells, monoclonal antibodies (MAbs) were raised against variant S49 mouse lymphoma cells. Immunoperoxidase analysis with a specific MAb, named M-66, revealed nuclear localization with prominent staining in the nucleoli of both tumorigenic (T-63) cells and nontumorigenic, immunogenic (T-25-Adh) cells. Weak signals were also observed in the cytoplasm and plasma membrane of both cells. Western blot analysis with M-66 antibody revealed a 14-kDa protein in nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…Although a variety of viral proteins are translocated into the nucleolus following viral infection (33), we were the first to show that the signal peptide of MMTV-Env precursor is also localized to this compartment (16,17). It turns out that this is not an isolated case, as it was recently shown that the leader sequence of HERV-K is also localized in the nucleolus (22).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Although a variety of viral proteins are translocated into the nucleolus following viral infection (33), we were the first to show that the signal peptide of MMTV-Env precursor is also localized to this compartment (16,17). It turns out that this is not an isolated case, as it was recently shown that the leader sequence of HERV-K is also localized in the nucleolus (22).…”
Section: Discussionmentioning
confidence: 73%
“…Previously, we showed that the signal peptide (98 Nterminal amino acids) of the Env-precursor protein of MMTV is localized in nucleoli of murine T-cell lymphomas that harbor the virus (16,17). This peptide was initially named MMTV-p14 (p14, for short) because of its electrophoretic mobility.…”
Section: Introductionmentioning
confidence: 99%
“…The best-documented association of MMTV with non-mammary tumors is with T cell lymphomas (1,2). Previously, we have shown that the leader peptide of the Env-precursor of MMTV is translocated from the cytoplasm to the nucleoli of murine T cell lymphomas (3,4). This protein, designated p14 based on Western blotting analysis, corresponds to the first 97 NH 2 -terminal amino acids of the MMTV 73 kDa Env-precursor, terminating just before the beginning of gp52 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…The mass of this protein determined by mass spectrometry is 11 kDa. p14 has been identified and characterized using a monoclonal antibody (M-66) generated against a cell surface epitope of T-25-Adh cells (3). T-25-Adh are nontumorigenic, immunogenic (substrate-adherent) cell variants derived from highly tumorigenic (suspension-borne) T-25 cells (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous data indicated that generation of full-length Rem or SP might be dependent on the cell line used for expression (2,11,12). Whole-cell extracts from mouse mammary tumor cells (GR-B2) expressing GR-strain MMTV were subjected to Western blotting with antibody prepared against the NLS/RNA-binding domain within the SP.…”
mentioning
confidence: 99%